3D profilometric characterization of the aged skin surface using a skin replica and alicona Mex software. Issue 3 (10th August 2015) - Pirisinu, Marco; Mazzarello, Vittorio
Summary: The skin's surface is characterized by a network of furrows and wrinkles showing different height and depth. Different studies showed that processes such as aging, photo aging and cancer may alter dermal ultrastructure surface. The quantitative analysis of skin topography is a key point for understanding health condition of the skin. Here, for the first time, the skin fine structure was studied via a new approach where replica method was combined with Mex Alicona software and scanning electron microscopy (SEM). The skin texture of cheek and forearm were studied in 120 healthy sardinian volunteers. Patients were divided into three different aged groups. The skin areas of interest were reproduced by the silicone replica method, each replica was explored by SEM and digital images were taken. By using Mex Alicona software were created 3D imagine and a list of 24 surface texture parameters were obtained, of these the most representative were chosen in order to assess eventual changes between groups. The skin's texture of forearm and cheek showed a gradually loss of its typical polyhedric mesh with increasing age group. In particular, the photoexposition increased loss of dermal texture. At today, Alicona mex technology was exclusively used on palaeontology studies, our results showed that a deep analyze of skin texture was performed and support Mex alicona software as a new promising tool on dermatological research. This new analytical approach provided an easy and fast process to appreciate skin texture and its changes, by using high quality 3D dimension images. SCANNING 38:213–220, 2016. © 2015 Wiley Periodicals, Inc.